2002
DOI: 10.1080/000163502753509455
|View full text |Cite
|
Sign up to set email alerts
|

VR1- and VRL-1-like immunoreactivity in normal and injured trigeminal dental primary sensory neurons of the rat

Abstract: The vanilloid receptor VR1 and the vanilloid receptor-like protein VRL-1 are associated with polymodal nociceptors, and may be important for pain processing in normal and injured teeth. Using immunohistochemistry, we have studied the distribution of these receptors in rat pulpal or gingival trigeminal ganglion neurons that were identified through retrograde labeling with fluoro-gold. Twenty-one percent to 34% of tooth pulp-innervating neurons were VRl-positive, while 32%-51% were VRL-1-immunoreactive. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 13 publications
3
50
1
Order By: Relevance
“…This leads to ion trapping of local anesthetic molecules in ionized form, causing a decrease in the number of local anesthetic molecules crossing the nerve membrane (8). Secondly, and a more accepted reason, is the activation of nociceptors by inflammatory mediators (8)(9)(10). In an uninjured or uninflamed pulp, the nociceptors are normally not activated by mild temperature or pH changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This leads to ion trapping of local anesthetic molecules in ionized form, causing a decrease in the number of local anesthetic molecules crossing the nerve membrane (8). Secondly, and a more accepted reason, is the activation of nociceptors by inflammatory mediators (8)(9)(10). In an uninjured or uninflamed pulp, the nociceptors are normally not activated by mild temperature or pH changes.…”
Section: Discussionmentioning
confidence: 98%
“…There are various proposed reasons to explain this phenomenon including a decreased local pH (8), tachyphylaxis of anesthetic solutions (8), accessory innervations (8), and the activation of nociceptors (8)(9)(10). The most plausible explanation is the inflammatory activation of tetrodotoxin and capsaicin-sensitive transient receptor potential vanilloid types 1 and 4 (8)(9)(10).…”
mentioning
confidence: 94%
“…There are also lesswell-characterized nociceptive receptors for other inflammatory molecules, including peptides (bradykinin), lipids (prostaglandins), and neurotrophins (NGF). Little is known about the distribution of nociceptive receptors in the periodontal tissues; however, a recent study has identified the VR1 receptor on about 25% of gingival neurones (Stenholm et al, 2002). Analysis of data from other tissues suggests that VR1 expression is limited to polymodal nociceptors on unmyelinated C fibers but that, during inflammation, A␦ neurones begin to express VR1 (Amaya et al, 2003).…”
Section: (8) Pain and Periodontitismentioning
confidence: 99%
“…The success rate of IANB drastically decreases, however, in patients with irreversible pulpitis 4,11,18,21,26) . Activation of nociceptors by inflammatory mediators such as prostaglandins (PGs) is considered a major cause of this phenomenon 3,6,20,24) . Nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit the chemical inflammatory mediators that activate or sensitize peripheral nociceptors 7) .…”
Section: Introductionmentioning
confidence: 99%